Reviving the Role of Customary Law as a Legal Foundation in the Development of the Indonesian Legal System - Rahayu, Iin (PT. Anagata Sembagi Education, 2024)
This research discusses the neglect of customary law as one of the sources of law in Indonesia, due to the perception that customary law is considered too traditional and unable to keep up with the times, such as globalization and technology. This research aims to explore areas of customary law that are still relevant in addressing the challenges faced by Indonesian society in the era of globalization, as well as to highlight the urgency of customary law as a foothold for national legal development policies. The research method used is descriptive analytical with a normative juridical approach. Data and information were obtained through interdisciplinary and multidisciplinary approaches as well as cross-sectoral, then analyzed in depth in a normative juridical manner. The results showed that several aspects of customary law, such as inheritance law, customary rights, pawn, rent, and profit sharing, still have relevance and can be a source of inspiration in the formation of national law and act as a source of law in the process of legal discovery.